PENGEMBANGAN MEDIA PAPAN PINTAR PENJUMLAHAN (PAPINJU) BERBASIS ANALISIS BERFIKIR KRITIS MELALUI PENINJAUAN GAYA BELAJAR PESERTA DIDIK SEKOLAH DASAR - Taripah, Taripah; Subali, Bambang; Widiarti, Nuni; Sutopo, Yeri; Yuwono, Agus (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This research aims to develop an interactive learning media of Addition Smart Board (PAPINJU) based on critical thinking analysis through reviewing the learning styles of elementary school students. The research method used the Research and Development (R&D) approach. The sample was selected using purposive sampling technique. Data were collected through a questionnaire instrument to identify learners' learning styles and a critical thinking skills test. The research participants were all grade 1 students of Bangsri 04 State Elementary School, whose learning styles were analyzed. A total of 15 learners were selected to represent three types of learning styles, with five learners for each type (visual, auditorial, and kinesthetic). The data analysis process was conducted through three main stages: data reduction, data presentation, and conclusion drawing. The results showed several findings: 1. learners with kinesthetic learning style show the ability to fulfill all indicators, including explaining simply, designing strategies, and drawing conclusions. 2. learners with auditorial learning styles are able to design strategies and draw conclusions, but are less than optimal in providing simple explanations. 3. learners with visual learning styles can provide simple explanations and design strategies, but have difficulty in drawing conclusions.